O‘ZBEKISTON ENERGETIKA TIZIMIDA QAYTA TIKLANUVCHI ENERGIYA ULUSHINI OSHIRISH STRATEGIYALARI (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
In this article, the current state of the energy system of Uzbekistan, the need to develop renewable energy sources, existing potential, ongoing projects and strategies for increasing the share are analyzed in depth. The potential of the country in solar, wind, hydropower and biomass is evaluated from a scientific point of view. The theoretical and practical bases of modernization of the energy system, improvement of the investment environment, attraction of the private sector, improvement of energy efficiency and introduction of scientific and technological innovations are covered. The results of the study show that increasing the share of renewable energy is an important factor for Uzbekistan's economic security, environmental stability and transition to a green economy.